THEORETICAL AND CONCEPTUAL PRINCIPLES OF THE MECHANISMS FOR SUSTAINABLE DEVELOPMENT FINANCING - Хмелярчук, Марія; Сундай, Імо (Socio-economic relations in the digital society, 2020)
The article is devoted to the study of theoretical and conceptual mechanisms of financing sustainable development goals at the national and international levels. Numerous scientific publications of scientists, international scientific-practical conferences, congresses and symposiums, which consider various sources and instruments of funding used to promote the sustainable development goals, taking into account the specifics of socio-economic development of different countries. The conceptual principles of financing sustainable development define the principle not only of economic but also social efficiency, which involves the use of various financial mechanisms to achieve key indicators of social and environmental stability in the world. From these positions the approaches of mechanisms of financing of sustainable development at the expense of the state allocations and investments, the credit mechanism of financing at the national and international levels, the international, public and private investments are considered. The author’s concept of sustainable development financing provides for the expediency of forming a system of mechanisms for adequate financing of sustainable development goals through international, national and private financial resources using various financial instruments and appropriate institutionalization of the financial system and sustainable development financing policy at national and international levels. According to the authors’ research, this approach is especially relevant for countries with developing economies and countries with economies in transition, where most of the sustainable development goals are unfulfilled, or lag behind and require significant resources to finance them.